2008
DOI: 10.1007/s12325-008-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different dose regimens of enoxaparin in deep vein thrombosis therapy in pregnancy

Abstract: Enoxaparin can be used safely in DVT therapy during pregnancy. Our results indicate that therapy consisting of a single daily dose of 1.5 mg/kg enoxaparin is as effective as twice-daily administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Among the selected studies, 17 were written in English [19,21–36] and one in German [20]. The corresponding authors of 11 of the selected studies were contacted, with the aim of obtaining missing information, and six authors kindly provided the requested data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the selected studies, 17 were written in English [19,21–36] and one in German [20]. The corresponding authors of 11 of the selected studies were contacted, with the aim of obtaining missing information, and six authors kindly provided the requested data.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies published as full articles, we further excluded one article because no antithrombotic therapy was used, seven because they included £ 10 patients, two because no data on follow-up were provided, and six because data on patients treated for acute VTE were not distinguishable from data on women receiving antithrombotic prophylaxis. Thus, a total of 15 full articles [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and three abstracts [34][35][36] were eligible for inclusion in our systematic review (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Given their equivalent efficacy and safety, the lower dose may be more cost-effective, but this has not been studied systematically. Neither the American College of Obstetrics and Gynecology nor 37 In contrast to prophylactic dosing, therapeutic dosing of LMWH is weight based. The more common LMWHs available in the United States, enoxaparin and dalteparin, are administered every 12 hours.…”
Section: Low-molecular-weight Heparinmentioning
confidence: 99%
“…Regrettably, among studies selected for our meta-analysis, information about epidural anesthesiology was scarce. In only two papers did the authors describe the protocol used for epidural anesthesia: regional anesthesia was avoided until at least 12 h after the last dose of low-molecular-weight heparin (LMWH), which in one study was reduced to a prophylactic dose on the day prior to induction of labour; LMWH was subsequently re-administrated after 3 or 4 h after catheter removal [1,2]. In three other studies the authors reported that women did not suffer from epidural hemorrhages, but information about the anesthesiologic procedure was not provided [3][4][5].…”
mentioning
confidence: 99%